PROFESIONALISME PUSTAKAWAN DALAM LAYANAN INFORMASI - Sri Anawati (Jurnal Pustaka Ilmiah, 2015)
Advances in science and technology are increasingly causing increased the needand demand pemustaka. Here librarians are required to be able to answer thesechallenges, in order to meet the needs user. Librarian is a profession that requires education or training to manage the library. The professionalism of librarians should be increased because the librarian is an important element in the library. If the library does not want to be left pemustaka and want to continue to progress and evolve, the librarian should develop a professional attitude in order to create a positive image. A professional librarian who not only required to master the skill and technique of the library, but his soul felt called to become a librarian and aware that the profession of librarian is the servant of the library patron.